Acute Basilar Artery Occlusion: Differences in Characteristics and Outcomes after Endovascular Therapy between Patients with and without Underlying Severe Atherosclerotic Stenosis - Lee, Y.Y. (AJNR Am J Neuroradiol, 2017)
BACKGROUND AND PURPOSE: Prediction of underlying intracranial atherosclerotic stenosis before endovascular therapy might be helpful for appropriate therapeutic planning in patients with acute ischemic stroke. This study aimed to compare the characteristics and treatment outcomes in patients with acute basilar artery occlusion relative to the existence or nonexistence of underlying intracranial atherosclerotic stenosis. MATERIALS AND METHODS: Sixty-two patients with acute basilar artery occlusion underwent multimodal endovascular therapy. All patients underwent stent-retriever thrombectomy as a first-line endovascular therapy. Patients with underlying intracranial atherosclerotic stenosis underwent additional intracranial angioplasty and stent placement. The clinical and imaging characteristics and treatment outcomes were retrospectively analyzed and compared between patients with and without intracranial atherosclerotic stenosis. RESULTS: Underlying intracranial atherosclerotic stenosis was identified at the occlusion site in 15 patients (24.1%). Occlusion in the proximal segment of the basilar artery was more common in patients with intracranial atherosclerotic stenosis (60% versus 6.4%, P < .001), whereas occlusion in the distal segment was more common in those without it (91.5% versus 26.7%, P < .001). Bilateral thalamic infarction on a pretreatment DWI was less common in patients with intracranial atherosclerotic stenosis (0% versus 27.7%, P = .027) compared with those without it. There were no significant differences in the rates of successful revascularization, favorable outcome, symptomatic hemorrhage, and mortality between the 2 groups. CONCLUSIONS: Underlying intracranial atherosclerotic stenosis was not uncommon in patients with acute basilar artery occlusion. The occlusion segment of the basilar artery and the presence or absence of bilateral thalamic infarction on a pretreatment DWI might be helpful for predicting underlying intracranial atherosclerotic stenosis in patients with acute basilar artery occlusion. Patients with and without underlying intracranial atherosclerotic stenosis who underwent endovascular therapy had similar outcomes.